Ivan Ilyin’s views on war and violence and their use among Russian religious and military audiences, 2005–2023 - Kytöneva, Santeri (Studies in East European thought, 2025)
Ivan Alexandrovich Ilyin (1883–1954) was a Russian philosopher whose writings have recently resurfaced among Russian political elites and in contemporary Russian Orthodox Church discourse. This article provides a reading of Ilyin’s main works on violence, The Basic Moral Contradiction of War (1914) and On Resistance to Evil by Force (1925), outlining how Ilyin’s texts have been utilised by both the Russian Orthodox Church and security service actors from 2005 to 2023. The case study demonstrates that Ilyin’s writings have been instrumentalised by these groups to support arguments in favour of soldiering and for a deeper connection between the church and the military. This article contributes to our understanding of religious militancy in Russian Orthodox discourse by examining an inherent tension in both Ilyin’s work and its reception among Russian religious and military audiences. The article concludes that both Ilyin and references to his works made by individuals associated with the Russian Orthodox Church rely on a problematically subjective conception of morality and attribute virtue to soldiering.